2005
DOI: 10.1097/01.mpg.0000182011.77322.97
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Depressive Severity in Adolescents With Inflammatory Bowel Disease

Abstract: Background: Although IgA endomysial antibodies (EMA) and tissue transglutaminase (TG) are sensitive and specific serologic tests for the diagnosis of celiac disease, there is limited information on the association of the magnitude of antibody level with the severity of the histological abnormalities of the intestine. Purpose: To determine if EMA and TG titers correlate with the severity of histological changes in patients with celiac disease. Methods: We identified 148 children from our laboratory database tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Two studies investigating the effects of steroids on mood and memory in children with IBD found that subjects on steroids had significantly more problems with verbal memory, working memory, and depression compared with youths not on steroids 23,24. Mixed results have been found for the relationship between age at diagnosis and more behavioral/emotional symptoms,11,18 although increasing age during adolescence was associated with increased depressive severity, independent of IBD severity 11,25…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies investigating the effects of steroids on mood and memory in children with IBD found that subjects on steroids had significantly more problems with verbal memory, working memory, and depression compared with youths not on steroids 23,24. Mixed results have been found for the relationship between age at diagnosis and more behavioral/emotional symptoms,11,18 although increasing age during adolescence was associated with increased depressive severity, independent of IBD severity 11,25…”
Section: Methodsmentioning
confidence: 99%
“…23,24 Mixed results have been found for the relationship between age at diagnosis and more behavioral/emotional symptoms, 11,18 although increasing age during adolescence was associated with increased depressive severity, independent of IBD severity. 11,25 To summarize, rates of psychiatric disorders in children with IBD vary a great deal, and many studies are limited by small sample sizes. The studies with larger samples reported lower rates (4% to 28%) than studies with small samples (59% to 73%).…”
Section: Behavioral/emotional Functioningmentioning
confidence: 99%